Evaluation of Cash and Bank Reconciliation Delays on the Effectiveness of Internal Control at XYZ Savings and Loan Cooperative - Fernanda Novia Pramitha; Endah Susilowati (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to evaluate the delay in cash and bank reconciliation on the effectiveness of internal control at Xyz Savings and Loan Cooperative. The research method used a descriptive qualitative approach with structured interview technique as the main instrument of data collection. The results showed that the delay in cash and bank reconciliation was caused by the main factor in the form of late confirmation of transactions from cooperative members which resulted in the emergence of unmatched transactions. This condition occurs quite often and has a significant impact on the effectiveness of internal control, causing delays in financial reports and discrepancies in reports on member deposits and receivables. Although the cooperative has implemented a technology system that is considered very effective and handling procedures through other accounts payable, reliance on member responsiveness as an external factor remains a systemic weakness. Improvement efforts through announcements on the coordinator's WAG have not fully addressed the root of the problem. This study concludes that there is a need to develop a more proactive communication system and implement real-time notification technology to strengthen the internal control system and minimize reconciliation delays in the future.